2014
DOI: 10.1007/s12035-014-9022-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Electroacupuncture on Neural Myelin Sheaths is Mediated via Promotion of Oligodendrocyte Proliferation and Inhibition of Oligodendrocyte Death After Compressed Spinal Cord Injury

Abstract: Electroacupuncture (EA) has been used worldwide to treat demyelinating diseases, but its therapeutic mechanism is poorly understood. In this study, a custom-designed model of compressed spinal cord injury (CSCI) was used to induce demyelination. Zusanli (ST36) and Taixi (KI3) acupoints of adult rats were stimulated by EA to demonstrate its protective effect. At 14 days after EA, both locomotor skills and ultrastructural features of myelin sheath were significantly improved. Phenotypes of proliferating cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 62 publications
5
27
0
Order By: Relevance
“…In a recent study, the research showed that EA can facilitate remyelination via promoting the proliferation of oligodendrocyte and inhibiting its death in SCI model (Huang et al, 2015), and here we report a new mechanism underlying the remyelinating effect of EA, which is by recruiting microglia into areas with demyelinating lesions to clear degraded myelin debris. However, further studies have to be conducted to understand the neural pathway and the precise molecular and cellular mechanisms of how EA regulate microglia recruitment, migration as well as polarization.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In a recent study, the research showed that EA can facilitate remyelination via promoting the proliferation of oligodendrocyte and inhibiting its death in SCI model (Huang et al, 2015), and here we report a new mechanism underlying the remyelinating effect of EA, which is by recruiting microglia into areas with demyelinating lesions to clear degraded myelin debris. However, further studies have to be conducted to understand the neural pathway and the precise molecular and cellular mechanisms of how EA regulate microglia recruitment, migration as well as polarization.…”
Section: Discussionsupporting
confidence: 67%
“…The results we obtained indicate that EA treatment enhances the expression of myelin-related components, which further support the results we obtained from behavioral tests. Together with previous research (Ding et al, 2013; Huang et al, 2015; Liu et al, 2015), we are inclined to conclude that EA is an effective healing method to facilitate remyelination in diseases with demyelination. However, we found a disparity in our RT-PCT results: the mRNA expression of MBP (also PLP1) at week 7 is not down-regulated whereas the expression of MBP detected by Western Blot and immuno-staining is reduced.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Model groups: the CSCI model (Additional File 1) was constructed based on a previous method developed by our group [5,6,21]. The rats were fasted 24 hours prior to surgery, anesthetized by intraperitoneal injection of 3.5% chloral hydrate and subjected to continuous oxygen inhalation.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…CSCI is usually caused by spinal tumors, spinal tuberculosis, vertebral fractures, epidural hematoma or other diseases [1][2][3][4]. Previous studies showed that demyelinating lesion is one of the important pathological changes of CSCI, while the apoptosis of OPCs is the main reason for demyelination after CSCI [5][6][7][8][9][10]. The nerve impulses of demyelinating nerve fibers become diffused during conduction, preventing the electrical conduction of axons and resulting in partial or complete inhibition of movement, sensation and sphincter functions below the level of injury [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%